Evaluating Good Governance in Preserved Forests: a Comparison Between Community-based and State-based Forest Management in South Sumatera - Pamungkas, Wahyu (FIA UB, 2018)
Preserved forest can provide important benefits in protecting life-support systems especially in water management, landscape protection, and soil fertilization maintenance. Unfortunately, in Indonesia, the existence of preserved forest is threatened by the high rate of deforestation, that is often associated with poor quality governance. This research aims to evaluate the applying of good governance principles in preserved forest at South Sumatera Province managed through two types of governance namely Community Based Forest Management (CBFM) and State Based Forest Management (SBFM). This paper also correlated between applying good governance principles with deforestation rate to understand the effect of good governance on management effectiveness. This research is a qualitative research by using semi structure interview. Evaluation method follows that developed by Lockwood (2009) using 5 of 7 principles of good governance namely transparency, accountability, fairness, connectivity, resilience and adaptability. This research reveals that SBFM gets an exemplary level in 2 principles and the rest earns a high-level performance. Meanwhile CBFM obtains a substantial level of desirable improvement for all principles. It can be concluded that SBFM is better than CBFM in applying good governance principles. Furthermore, analysing of GIS reveal that deforestation rate in SBFM higher than SBFM in the period 2011-2015 recorded for 9.84% and 6.37% respectively. In term of correlation between good governance and deforestation, this study reveals that better in application of good governance principles did not lead to lower deforestation rate. Further research is required to understand the difference between the result of this research and the supporting theories in terms of the effect of good governance to management effectiveness. Keyword: Preserved forest, Good Governance, Deforestation, Stated Based Forest Management, Community Based Forest Management, South Sumatera.